Pengaruh Kebijakan Dividen dan Earning Per Share dengan Pertumbuhan Laba sebagai Variabel Moderasi terhadap Harga Saham pada Perusahaan Pelayaran yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Safira, Moza; Azzahra, Firza; Gultom, Parapat (ARZUSIN, 2024)
This research aims to analyze the influence of dividend policy and earnings per share (EPS) on the share prices of shipping companies which are influenced by profit growth listed on the Indonesia Stock Exchange for the 2019-2023 period. This research uses a quantitative approach with the moderated regression analysis method used to test the research hypothesis. The results of the analysis show that partially, dividend policy and EPS do not have a significant effect on shipping company share prices. Likewise, the profit growth variable does not have a significant effect on share prices partially. Furthermore, profit growth cannot moderate the relationship between dividend policy and EPS on share prices. Simultaneously, dividend policy, EPS, profit growth, as well as the interaction between dividend policy and profit growth and the interaction between EPS and profit growth also do not have a significant effect on stock prices.